A double-blind, placebo-controlled randomized comparison of pre and postoperative administration of ketorolac and tramadol for dental extraction pain - Hitesh Mishra; Farhan Ahmad Khan (Wolters Kluwer Medknow Publications, 2012)
Objective : To compare the analgesic efficacy and safety of single-dose oral ketorolac and tramadol administered pre and postoperatively for dental extraction pain. Materials and Methods: 74 patients undergoing third molar extraction (impacted or other causes) were recruited into the study, over a period of 1 year. The patients were divided into six groups and they were given ketorolac (20 mg), tramadol (100 mg), or placebo either preoperatively or postoperatively (half an hour before or half an hour after the procedure). Placebo was glucose powder filled in empty capsule. Pain assessment was done using a modified Verbal Rating Scale (VRS) at 30 min, 2, 4, and 6 h after the procedure. A record of whether rescue analgesic (ibuprofen 400 mg) was taken during the 6 h study period, along with the time it was taken, was made. Record of any adverse effects experienced by the patient was also kept. Maximum pain scores for each of the six study groups, over the 6 h study period, were noted. Results: Ketorolac and tramadol were significantly better than placebo in relieving molar tooth extraction pain. Postoperative administration of tramadol was found to be more efficacious than preoperative administration in relieving the pain, whereas the preoperative administration of ketorolac was better than its postoperative administration. Conclusion: This study demonstrated that tramadol is equally effective to ketorolac in relieving pain in the first 6 h after molar extraction and therefore can be tried in patients who are intolerant to nonsteroidal anti-inflammatory drugs.